Implementasi Pendidikan Berbasis Waldorf Melalui Bimbingan Belajar pada Anak Usia Dini - Aisyatin Kamila (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
One alternative choice for parents to provide education to children as an effort to solve various educational problems is the presence of tutoring. Choosing a learning model is very important, because it is able to optimize all aspects of a child's development. Waldorf is a learning model coined by Rudolf Steiner. The aim of this research is to find out how the Waldorf learning model is implemented through tutoring for early childhood at the Al Amin Wonorejo tutoring school. The research method used is descriptive qualitative. Data collection used observation, interview and documentation techniques regarding the Waldorf learning model through tutoring for early childhood, where checking the validity of the data used source triangulation techniques. The results of this research explain that Waldorf education-based tutoring produces stimuli in the form of: 1) children's creativity, 2) children's analytical skills, 3) independence, and 4) children's imagination.